On the microstructure of magnesium thin films deposited by magnetron sputtering - Moens, Filip; Schramm, Isabella Citlalli; Konstantinidis, Stéphanos; Depla, Diederik (Thin solid films, 2019)
Direct current magnetron sputtering (DCMS), and high power impulse magnetron sputtering (HiPIMS) are used to deposit magnesium thin films. The latter technique is characterized by a higher degree of ionization and an ion energy distribution which is significantly altered towards a higher mean ion energy. These differences between both techniques are also reflected in the obtained microstructure of the deposited Mg thin films. DCMS grown films present a rough surface, a porous microstructure and tilted columns, while films deposited by HiPIMS are smooth, dense and have straight columns. Energy and time resolved mass spectrometry show a distinct difference regarding the ion bombardment at the substrate level. The observed film differences are connected to structure zone models with as main focus the role of ion bombardment in the microstructural evolution. •Model for the microstructural evolution of sputter deposited Mg thin films•Film porosity during DC sputter deposition linked with material properties•Magnesium film density controlled by HiPIMS off pulse duration